International trade and agriculture : theory and policy - Hillman, Jimmye S.; Schmitz, Andrew (Boulder, Colo. : Westview Press, 1979)
This book focuses on research needs in the field of international trade and agriculture.
Includes index.
Includes bibliographical references: p. 299-321.
ijb 17/01/2019
Loans
Keywords: Agriculture; Commerce; United States